TRAINING TO MAINTAIN A SENSE OF BUFFERING IN THE MHXS ASSYRIA IN THE WORKPLACE (Academicia Globe: Inderscience Research, 2023)
In this case, the MHXS assortment of buffers was discussed in the midst of a period of time.